Methodical approach to assessing the effictiveness of combat training based on the s-shaped functions, taking into account the influence of the factor of sufficiency of funding - Semenenko , Oleg; Boiko , Ruslan; Semenenko , Liliya; Moskalenko , Igor (Social Development and Security, 2020)
Today, the leadership of the Armed Forces of Ukraine and the state as a whole often focuses on the need to improve the existing system of training of the Armed Forces of Ukraine both by increasing the priority of financing training activities in development plans and programs of the Armed Forces of Ukraine and by changing approaches to assessing their effectiveness. reporting period. The authors present a methodical approach to assessing the effectiveness of combat training based on the use of S-shaped functions, taking into account the influence of the factor of adequacy of funding on the level of training of military personnel, as well as a list of basic recommendations for the sequence of actions of combat training. services of the types of the Armed Forces of Ukraine and the Armed Forces in general, taking into account the application of such an approach. The basis of the proposed methodological approach to assessing the effectiveness of combat training of the Armed Forces of Ukraine, taking into account changes in the adequacy of their funding, models are proposed, which are used to describe the functioning of complex systems in systems engineering. The application of the theory of S-shaped functions during the optimization of performance indicators of the Ukrainian Armed Forces development programs in the direction of “Combat training” taking into account the level of adequacy of projected funding, will ensure optimal planning of planned combat training activities and maximize the effect of planned activities conducting combat training in the Armed Forces of Ukraine, as well as the reliability of the expected results of the planned activities, taking into account the amount of allocated financial resources. The main practical significance of the proposed approach is that it gives a preliminary quantitative view of the expected results of combat training activities, taking into account the impact of the factor of adequacy of funding for these activities, which will be characterized by the level of training of personnel, taking into account the situation of their funding. requirements.